A damping boundary condition for atomistic-continuum coupling. (May 2017) - Zhang 张, Jie 杰; Tieu, Kiet; Michal, Guillaume; Zhu 朱, Hongtao 洪涛; Zhang 张, Liang 亮; Su 苏, Lihong 利红; Deng 邓, Guanyu 关宇; Wang 王, Hui 辉
Abstract : The minimization of spurious wave reflection is a challenge in multiscale coupling due to the difference of spatial resolution between atomistic and continuum regions. In this study, a new damping condition is presented for eliminating spurious wave reflection at the interface between atomistic and continuum regions. This damping method starts by a coarse–fine decomposition of the atomic velocity based on the bridging scale method. The fine scale velocity of the atoms in the damping region is reduced by applying nonlinear damping coefficients. The effectiveness of this damping method is verified by one- and two- dimensional simulations.